(untitled) (Sociologisk Forskning, 2019)
This paper discusses modern organizational meetings in the public sector, with a focus on time, specifically the planning and scheduling of time among managers. In this qualitative analysis, data were gathered through an ethnographic study of managers in several public organizations, all in Sweden. During interviews and field observations, managers told about their time work involving strategies for dealing with their fully booked calendars, or for handling what they described as boring or meaningless meetings. These strategies can be conceptualized as a form of ”meeting resistance” among the managers in these organizations. Their retold experiences and strategies raise issues of meeting resistance in relation to the meetingization of contemporary work life and, in a wider sense, questions of power and control over time at work. By using a variety of strategies for negotiating and resisting the rule of the calendar, managers may achieve a greater sense of control over their time. Nevertheless, despite their strategies and resistance, the machinery of meetings is hard to stop due to an Eigendynamik of meetings.